An automated transmitter positioning system for misalignment compensation of capacitive-coupled electric vehicles - Md. Nazrul Islam Siddique; Nadim Ahmed; Saad Mohammad Abdullah; Md. Ziaur Rahman Khan (International Journal of Electrical and Computer Engineering (IJECE), 2022)
Misalignments are one of the most unfavorable aspects of the capacitive power transfer (CPT) system, which is inevitable in most of the applications. Misalignments affect the overall resonances in the circuit and decrease the power transfer capability and efficiency. In this paper, an automated electro-mechanical transmitter positioning system is proposed for capacitive wireless charging to withstand both axial and rotational misalignments. The system can align the transmitter based on an adaptive algorithm, with respect to the position of the receiver to mitigate the misalignments. The overall system is designed using SolidWorks and the algorithm is verified using Processing. Then, a hardware prototype is constructed in the laboratory. The accuracy of the proposed system is calculated and compared with the simulation results. The system can achieve an accuracy of 99.5%, in case of axial misalignment and an average accuracy of 98.6%, in case of both axial and rotational misalignments, which validate the simulation results.